Racial Oppression, Black Consciousness and the Quest for Freedom in Peter Abrahams’ Mine Boy (1946) - Babacar Diakhaté (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The white South African capitalist system deprived the rural population of their lands. This deprivation of their cultivating lands engendered the displacement of the proletariat class to the city to find a better life. In 1946, Peter Abrahams released Mine Boy to denounce the exploitation and oppression of the blacks by white people. This article aims at castigating the inhuman treatment reserved for Xuma, a village rural boy who goes to Johannesburg to improve his economic situation in the mine. Xuma’s predicaments and Johannes and Chris’ deaths in the mines illustrate the brutal attitudes of the white bosses towards their mineworkers. The rising consciousness of the mineworkers leads them to a perpetual liberation struggle that finally ends in their historical freedom.